2021
DOI: 10.1177/0194599820982914
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Conflict of Interest and Published Position on Hypoglossal Nerve Stimulation for Sleep Apnea

Abstract: Objective To determine if there is an association between authors’ financial conflict of interest and published position on clinical use of hypoglossal nerve stimulation for obstructive sleep apnea. Study Design Retrospective cross-sectional analysis. Setting International roster of authors and articles analyzed. Methods A Google Scholar search was performed for editorials and reviews citing the 2014 New England Journal of Medicine article on hypoglossal nerve stimulation for obstructive sleep apnea. Included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…For instance, receiving general payments by authors was associated with positions favourable to the funding companies expressed in editorials, guidelines and review articles. 50 While some studies have documented an association between general payments, 51 including consultancies, 52 and positive clinical trial outcomes, others have established no such relationship. 53 Further, undisclosed general payments, detected by comparing Open Payments with researchers’ self-reporting, are widespread in articles presenting findings from research studies, 54 - 56 including reports of clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, receiving general payments by authors was associated with positions favourable to the funding companies expressed in editorials, guidelines and review articles. 50 While some studies have documented an association between general payments, 51 including consultancies, 52 and positive clinical trial outcomes, others have established no such relationship. 53 Further, undisclosed general payments, detected by comparing Open Payments with researchers’ self-reporting, are widespread in articles presenting findings from research studies, 54 - 56 including reports of clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a recent study by Crossley et al reported a potential bias in HNS studies, since research has been sponsored by manufacturers of the stimulation devices [ 85 ]. Though this imposes a conflict of interest, it is common for early clinical research in absence of sufficient funding for these activities.…”
Section: Limitationsmentioning
confidence: 99%